The role of confocal scanning laser ophthalmoscopy in stereometric differentiation of eye papilla in ocular hypertension, normal tension glaucoma and primary open-angle glaucoma - Gvozdenović Ranko; Risović Dušica; Marjanović Ivan; Stamenković Miroslav; Joković Zorica; Abazi Zihret (Vojnosanitetski Pregled)
Background/Aim. Primary open angle glaucoma (POAG) and normal tension glaucoma (NTG) demonstrate the same structural changes in the optic disc along with visual field defects but only POAG includes an abnormal elevation of intraocular pressure. Heidelberg retina tomograph based on confocal scanning laser ophthalmoscopy (HRT) and Moorfields regression analysis (MRA) have been employed to quantitatively assess the topography of eye papilla. We measured stereographic parameters of eye papilla in patients with POAG, NTG, and ocular hypertension (OH) using an HRT in order to determine whether HRT topographic parameters can be used to differentiate those conditions. Methods. The results of 145 eyes of 145 patients with OH, NTG and POAG were analyzed by age, refractive error, quality of HRT images, stereometric and MRA parameters. Results. Significant differences were found between NTG and other two groups for a majority of the HRT parameters, and also no differences between OH and POAG patients for a majority of the investigated parameters, except thickness of retinal nerve fiber layer. By reading the MRA no differences were found in the distribution of mostly damaged and mostly preserved neuroretinal rim sectors between NTG and POAG patients, and also all sectors of the neuroretinal rim in OH patients were preserved. Conclusion. HRT stereometric parameters are useful to differentiate patients with OH and NTG, and also for differentiation between NTG and POAG patients, but most of parameters showed no difference between OH and POAG patients. MRA may serve to confirm the diagnosis of OH, but not for precise distinction between NTG and POAG.